The Influence of AI Knowledge and Business Ethics Understanding on Student Perceptions and Acceptance of Sustainable Business Transformation - Okto Irianto; Henie Poerwandar Asmaningrum (The Faculty of Teacher Training and Education (FKIP), Universitas Sebelas Maret, Indonesia, 2025)
This study examines how students' understanding of Artificial Intelligence and business ethics influences their perceptions and acceptance of AI in sustainable business transformation. Using a quantitative approach with stratified random sampling, data were collected from 450 undergraduate students in the Faculty of Economics and Business, representing Management (40%), Accounting (35%), and Development Economics (25%). Multiple regression analysis revealed significant positive relationships between AI understanding and both perception (β = 0.485, p < 0.001) and acceptance (β = 0.423, p < 0.001) of AI in sustainable business. Similarly, business ethics understanding significantly influenced perception (β = 0.372, p < 0.001) and acceptance (β = 0.356, p < 0.001). The research model explained 64.3% of variance in perceptions and 58.7% in acceptance of AI for business sustainability. Management students demonstrated higher understanding (mean = 3.95) compared to other majors. These findings highlight a critical gap in contemporary business education: the need to integrate technological knowledge with ethical frameworks and sustainability principles. Educational institutions must develop comprehensive curricula that prepare future business leaders for ethical digital transformation. This research contributes valuable insights for curriculum developers and policymakers seeking to align business education with the evolving demands of AI-driven sustainable business landscapes.